SUBJECTIVE TRANSFORMATION OF THE SITUATION IN THE SYSTEM OF DECISION-MAKING OF THE PERSONALITY - Sannikov, Aleksandr (PSYCHOLOGICAL JOURNAL, 2017)
The article presents the results of an analysis of the mechanism of choice and decision-making by the personality. The existing ideas about the choice, decision-making and the correlation between them in the works of domestic and foreign scientists are described. It is found that the decision-making is a consequence of subjective transformations of the life situation. Classification of real and virtual life situations is proposed. The content, components and psychological essence of the studied phenomenon - the subjective transformation of the situation - are specified. The author’s concept of the psychological system of decision-making by the personality is offered. The basic concepts are defined and the interpretation of the system elements is given: decision, life decision, situation, life situation, virtual situation, decision-making criteria. The criteria for the correspondence of the decision to the requirements of the system are singled out: situationality of the life decision, structural integrity, functional and subjective utility. The functions and actions performed by the decision-making system on each transformation are described. The activity of various combinations of system components on each transformation is shown. The results of the analysis and the structural diagram of the given psychological system, the features of the transformation of the life situation, aimed at the choice, acceptance and implementation of the decision by the personality are presented.